4. If the centroid of a triangle is at (1, 3) and two of its vertices are (-7, 6) and (8, 5) then
find the third vertex of the triangle .
Answers
Answered by
7
Hi ,
******************************************
#Centroid of the triangle :
The centroid of the triangle formed
by the points A( x1 , y1 ) , B( x2 , y2 ),
C( x3 , y3 ) is
( x1 + x2 + x3 /3 , y1 + y2 + y3/3 )
*******************************************
Let the third vertex = ( x , y )
Centroid of the triangle whose
vertices are ( -7 , 6 ) ,( 8 , 5 ) and (x ,y)
is ( 1 , 3 )
( -7 + 8 + x /3 , 6 + 5 + y /3 ) = ( 1 , 3 )
( 1 + x/3 , 11 + y/3 ) = ( 1 , 3 )
***************************************
If ( a , b ) = ( c , d ) then
a = c , b = d
****************************************
(1 + x) /3 = 1
1 + x = 3
x = 3 - 1
x = 2 ,
And
( 11 + y )/3 = 3
11 + y = 9
y = 9 - 11
y = - 2
Therefore ,
Third vertex = ( x , y ) = ( 2 , - 2 )
I hope this helps you.
: )
******************************************
#Centroid of the triangle :
The centroid of the triangle formed
by the points A( x1 , y1 ) , B( x2 , y2 ),
C( x3 , y3 ) is
( x1 + x2 + x3 /3 , y1 + y2 + y3/3 )
*******************************************
Let the third vertex = ( x , y )
Centroid of the triangle whose
vertices are ( -7 , 6 ) ,( 8 , 5 ) and (x ,y)
is ( 1 , 3 )
( -7 + 8 + x /3 , 6 + 5 + y /3 ) = ( 1 , 3 )
( 1 + x/3 , 11 + y/3 ) = ( 1 , 3 )
***************************************
If ( a , b ) = ( c , d ) then
a = c , b = d
****************************************
(1 + x) /3 = 1
1 + x = 3
x = 3 - 1
x = 2 ,
And
( 11 + y )/3 = 3
11 + y = 9
y = 9 - 11
y = - 2
Therefore ,
Third vertex = ( x , y ) = ( 2 , - 2 )
I hope this helps you.
: )
Answered by
0
Answer:
The centroid of the triangle formed
by the points A( x1 , y1 ) , B( x2 , y2 ),
C( x3 , y3 ) is
( x1 + x2 + x3 /3 , y1 + y2 + y3/3 )
Let the third vertex = ( x , y )
Centroid of the triangle whose
vertices are ( -7 , 6 ) ,( 8 , 5 ) and (x ,y)
is ( 1 , 3 )
( -7 + 8 + x /3 , 6 + 5 + y /3 ) = ( 1 , 3 )
( 1 + x/3 , 11 + y/3 ) = ( 1 , 3 )
If ( a , b ) = ( c , d ) then
a = c , b = d
(1 + x) /3 = 1
1 + x = 3
x = 3 - 1
x = 2 ,
And
( 11 + y )/3 = 3
11 + y = 9
y = 9 - 11
y = - 2
Therefore ,
Third vertex = ( x , y ) = ( 2 , - 2 )
Step-by-step explanation:
Similar questions